Questionnaire for classification of cigarette consumers. Results obtained from its implementation in Cuba, 2017 - Justo Reinaldo Fabelo Roche; Serguei Iglesias Moré; Elisa Marlene Álvarez Martínez (Universidad de Ciencias Médicas de La Habana, 2019)
Introduction: Tobacco consumption becomes an addictive disorder that endangers the health of both smokers and those around them. Its proper evaluation requires an analysis of the psychological and social factors that favor it. Objective: To describe the adaptation process of the questionnaire for classification of cigarette consumers within the Cuban context and characterize the sample of smokers under study. Material and Methods: The research includes two stages: the first stage that is classified as a technological development study, and the second one which consists of a descriptive cross-sectional study with a quantitative design. Five experts and 205 active smokers selected from an intentional sample from the health areas of Havana and Santiago de Cuba participated in the study. Results: A valid version of the questionnaire for the Cuban population was developed, which contains the recommendations made by the experts and obtained an internal consistency of 0.7005. It was observed that 49.7% of the participants classified as strong smokers and 48.3% as moderate smokers (at risk). On the other hand, 60% of them are men, 32.7% are young and 65% are workers.  Conclusions: Linguistic and cultural adaptation to the Cuban context of the questionnaire for classification of cigarette consumers was carried out, which has an adequate level of reliability. Most of the subjects studied were classified as strong or moderate smokers. The male sex, young and workers predominated in the study. Keywords: Addiction, cigarettes, nicotine, classification of smokers, validation, linguistic adaptation.